Backpacker conceptualisation criteria: discussion, clarification and operationalisation proposal - Martins, Márcio Ribeiro (2023)
Purpose – Backpackers can be found all over the world, especially in urban areas where the main enclaves are established. The purpose of this paper is to discuss the operationalisation of the term ‘‘backpacker’’ and present a proposal to conceptualise backpackers and backpackers’ segments based on the operational criteria available in literature to avoid incongruities among researchers. Design/methodology/approach – Based on a literature review, this study provides a critical review of the backpacker conceptualisation and operationalisation using amethodology divided into three phases, a quantitative analysis based on the Scopus database and a bibliometric analysis coupled with a manual analysis of documents (content analysis). Findings – Substantial heterogeneity and complexity regarding the conceptualisation of backpacker tourism and its diversified subsegments were evident. For this reason, this paper argues that backpacker tourism can and should continue to be analysed from different perspectives, suitably framed in the theoretical instrument constructed to identify and distinguish the different subsegments through its operationalisation features. Originality/value – This study provides a practical contribution to all researchers interested in the topic of backpackers proposing the operationalisation of the term backpacker and it subsegments to avoid disparate results and deviations. This contribution will enable the correct and objective assessment of the operationalisation of this concept for researchers, managers and destination management organisations, identifying exactly what phenomenon is to be studied.